Answer:
m∠Q ≈ 53°
Step-by-step explanation:
To find the measure of ∠Q, the law of cosines will need to be used. Lowercase letters represent the side lengths, while upper case letters represent angles.
In this situation, 'A' will be ∠Q. Therefore:
17² = 18² + 20² -2(18)(20)cosQ
Simplify:
289 = 324 + 400 -2(360)cosQ
Continue simplifying down:
-435 = -720cosQ
Divide both sides by '-720':
0.604 = cosQ
![cos^{-1}Q = 0.604](https://tex.z-dn.net/?f=cos%5E%7B-1%7DQ%20%3D%200.604)
m∠Q ≈ 52.83 or 53° rounded to the nearest whole degree.
Hi there!
Something really good to remember about trigonometry is SOHCAHTOA. I won’t dive into too much detail about it, but you should google it for future assignments.
Anyways,
tan50°=14/AB
ABtan50°=14
AB=14/tan50°
AB=11.75
cos50°=14/AC
ACcos50°=14
AC=14/cos50°
AC=21.78
For the measure of angle C you can use a theorem called the third angle theorem. In every single possible triangle, the sum of all three angles adds up to 180°. You can set up an equation like so...
angleC=180-(90+50)
angleC=180-140
angleC=40°
Answer:
A = (1/2)(base)(height)
Step-by-step explanation:
Yes, that's correct:
A = (1/2)(base)(height)
Was there more to this question?
2 divided by 18 is 9 and 3 divided by 18 is 6 hope that helps
Answer:
(0,6)
Step-by-step explanation:
The given system of equations is
![y = \frac{3}{2}x + 6](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B3%7D%7B2%7Dx%20%2B%206)
and
![\frac{1}{2}y - \frac{1}{4}x = 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7Dy%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203)
We substitute the first equation into the second equation to get:
![\frac{1}{2} ( \frac{3}{2}x + 6) - \frac{1}{4}x = 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20%28%20%5Cfrac%7B3%7D%7B2%7Dx%20%2B%206%29%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203)
We expand to get:
![\frac{3}{4} x + 3 - \frac{1}{4}x = 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20x%20%2B%203%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203%20)
We group similar terms to get:
![\frac{3}{4}x - \frac{1}{4}x = 3 - 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7Dx%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203%20-%203)
![\frac{1}{2}x = 0](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7Dx%20%3D%200)
![x = 0](https://tex.z-dn.net/?f=x%20%3D%200)
Put x=0 in to the first equation to get:
![y = 6](https://tex.z-dn.net/?f=y%20%3D%206)
Therefore the solution is (0,6)